Atomic scale imaging of reversible ring cyclization in graphene nanoconstrictions - Lee, J; Lee, G; Lee, S; Yoon, E; Anderson, H; Briggs, G; Warner, J (American Chemical Society, 2019)
We present an atomic level study of reversible cyclization processes in suspended nanoconstricted regions of graphene that form linear carbon chains (LCCs). Before the nanoconstricted region reaches a single linear carbon chain (SLCC), we observe that a double linear carbon chain (DLCC) structure often reverts back to a ribbon of sp2 hybridized oligoacene rings, in a process akin to the Bergman rearrangement. When the length of the DLCC system only consists of ∼5 atoms in each LCC, full recyclization occurs for all atoms present, but for longer DLCCs we find that only single sections of the chain are modified in their bonding hybridization and no full ring closure occurs along the entire DLCCs. This process is observed in real time using aberration-corrected transmission electron microscopy and simulated using density functional theory and tight binding molecular dynamics calculations. These results show that DLCCs are highly sensitive to the adsorption of local gas molecules or surface diffusion impurities and undergo structural modifications.